Resources of history learning in conventional and modern continuum lines - Leli Yulifar; Aman Aman (LPMPP Universitas Negeri Yogyakarta, 2023)
In the field of history education, there are still educators who rely primarily on themselves as the main source of knowledge. However, history learning resources are diverse and encompass a wide range of materials based on historical content, which can be utilized based on the teacher’s creativity. This study aims at identifying and evaluating the use historical content-based history learning resources, both in theory and in practical implementation. To achieve this, a literature review was conducted, involving the collection of data from books, journals, notes, research reports, and internet sources. The process involved identification, conceptualization, and interpretation of the gathered information. The analysis reveals that historical content-based history learning resources exist on a continuum between conventional and modern sources. Rather than being mutually exclusive, these sources can complement each other. The discussion incorporates Edgar Dale's Cone of Experiences theory and examines benchmarks such as national archives and museums, as well as the History Education Doctoral Study Program of Faculty of Social Sciences Education (FPIPS) of Universitas Pendidikan Indonesia (UPI). In conclusion, historical content-based history learning resources offer an alternative approach that provides valuable insights to history educators beyond the confines of formal classroom settings. Educators can utilize both newly designed history learning resources and existing resources tailored to their specific needs and learning objectives